2015
DOI: 10.1007/s10682-015-9758-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimal foraging behavior with an explicit consideration of within-individual behavioral variation: an example of predation

Abstract: Animal behavior is flexible, and the same individual can exhibit variable expressions under the equivalent ecological situations (i.e., within-individual behavioral variation). This study examines the evolution of within-individual behavioral variation using an individual-based model. A common predation scenario is considered where a predator spends a period h to handle and consume a captured prey. The model assumes the handling time of the predator to be a random variable. The average and within-individual va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(32 reference statements)
0
2
0
1
Order By: Relevance
“…Bell et al 24. estimated that about 63% of behavioural variation results from IIV, and theoretical studies have suggested that it may be a trait on which selection can also act1925, but empirical studies on the effects of IIV on animal fitness are scarce. Intra-individual variability may be a form of adaptive variation in behaviour related to predator-prey interactions either to facilitate trial-and-error learning or to reduce vulnerability to predators21.…”
mentioning
confidence: 99%
“…Bell et al 24. estimated that about 63% of behavioural variation results from IIV, and theoretical studies have suggested that it may be a trait on which selection can also act1925, but empirical studies on the effects of IIV on animal fitness are scarce. Intra-individual variability may be a form of adaptive variation in behaviour related to predator-prey interactions either to facilitate trial-and-error learning or to reduce vulnerability to predators21.…”
mentioning
confidence: 99%
“…In other words, this is the degree to which an individual behaves differently in identical situations. Predictability has started to gain more attention only recently and therefore its adaptive function and the factors that influence it remain poorly understood ( Pruitt et al 2011 ; Stamps et al 2012 ; Biro and Adriaenssens 2013 ; Westneat et al 2015 ; Okuyama 2015 ; Stamps 2016 ).…”
mentioning
confidence: 99%
“…Los modelos de forrajeo óptimo han sido ampliamente utilizados para evaluar la manera en la que el comportamiento de un individuo puede afectar a la aptitud biológica en base a los costes y beneficios de obtener recursos (Bettinger et al, 2015;Bird y O'Connell, 2006;Byers y Ugan, 2005;Marlowe, 2005;Okuyama, 2015;Rodríguez et al, 2019;Simms, 1985;Smith y Winterhalder, 1992). En este sentido, cabe señalar que incluso ligeros cambios en el balance energético debido a un incremento en los costes de la actividad física pueden ser determinantes para el éxito reproductivo (Caldwell y Hooper, 2017;Urlacher y Kramer, 2018).…”
Section: Implicaciones Evolutivas De La Relación Entre Las Variables Antropométricas Y El Coste De La Locomociónunclassified